The Use of Simulation Technique to Improve Students' Speaking Skills - Aprilliai, Aprillia; Andayani, Endang Sri; Sulistyawati, Meiva Eka Sri (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
The objective of this study is to enhance students' oral proficiency through the use of the simulation technique. The research was conducted using classroom action research based on the Kemmis and Taggart model. The research participants were 30 English majors. This research demonstrates that integrating simulation into language teaching can yield measurable improvements in students' speaking proficiency, providing educators with a practical tool for enhancing oral communication skills. The findings revealed a substantial enhancement in their speaking abilities. The mean pre-test score rose from 58.1 to 67.8 (a 16.7% increase) in the first cycle and further improved to 85.2 (a 25.7% increase) in the second cycle, resulting in a total improvement of 46.6%. These results suggest that implementing the simulation technique can effectively enhance students' speaking skills, as demonstrated by the significant gains in mean scores and overall performance across the research cycles.